적분슬라이딩모드와 DOB를 이용한 강인추종 및 인간순응 로봇제어 - 아브너 어시그네시온(Abner Asignacion Jr); 김민찬(Min-chan Kim); 곽군평(Gun-Pyong Kwak); 박승규(Seung-kyu Park) (한국정보통신학회논문지, 2017)
The robot control with safety consideration is required since robots and human work together in the same space more frequently in these days. For safety, robots must have compliance to human force and robust tracking performance with high impednace for the nonhuman disturbances. The novel idea is proposed to achieve the compliance and high impedance with one controller structure. For the compliance, the ISMC(Integral Sliding Mode Control) and HDOB(Human Disturbance Observer) The human force is identified by using the human band pass filter and its output is sent to the sliding surface. The sliding mode dynamic is affected by human disturbance and the compliance for human is achieved. The disturbances besides human frequencies are decoupled by the ISMC and the robust tracking is achieved. The additional LDOB(Low Frequency Disturbance Observer) decreases the maxim nonlinear gain and leads low chattering. The introduction of human disturbance into the sliding mode dynamic is the main novel idea of this paper. 인간과 로봇이 같은 공간에서 작업을 할 경우가 많아짐에 따라 안전성을 고려한 로봇의 제어가 필요하다. 안정성을 위해서 로봇은 인간의 힘에 순응해야 함으로 낮은 임피던스가 요구되는 반면에 높은 제어성능을 갖도록 하기 위해서는 외란에 강인하기 위해서는 높은 임피던스가 요구된다. 이러한 이율배반적인 목적을 달성하기 위해서 본 연구에서는 적분슬라이딩모드와 외란관측기(DOB)를 사용하여 인간의 힘 이외의 외란에는 강인한 특성을 보이고 인간의 힘에는 순응할 수 있는 제어기를 설계한다. 인간의 동작이 특정 주파수의 범위에 있다는 사실에 근거하여 인간에 의한 외란인 경우의 외란에 대해서는 로봇이 순응하도록 슬라이딩모드를 설계하는 것이 본 논문의 독창적인 아이디어이다.